Embedding English Language in an Accounting Subject: A Case of Interactive Interdisciplinary Collaboration and Learning - Chatterjee, Bikram; Brown, Alistair (e-JBEST, 2012)
The paper outlines the development of a flow-chart solutions as the first step towards the development of a computer-based tool to enhance students’ learning of the topic ‘The IASB Framework.’ The co-ordinator of a Financial Accounting subject participated in an English language embedded program with English language specialists to facilitate students’ learning of this topic that requires step-by-step approach to problem solving. Facilitating students’ understanding of a discipline requires understanding of the language. Hence the study encourages future interdisciplinary collaboration to facilitate embedding English language development to enhance students’ learning of discipline based subjects.